Improving Youth Question-Asking and Provider Education during Pediatric Asthma Visits - Sleath, Betsy (Patient Educ Couns, 2018)
OBJECTIVE: We conducted a pragmatic randomized controlled trial to test the effectiveness of an asthma question prompt list with video intervention to increase youth question-asking and provider education during visits. METHODS: English or Spanish-speaking youth ages 11–17 with persistent asthma and their parents were enrolled from four rural and suburban pediatric clinics. Youth were randomized to the intervention or usual care groups. Intervention group adolescents watched the video on an iPad and then completed an asthma question prompt list before their visits. Generalized estimating equations were used to analyze the data. RESULTS: Forty providers and 359 patients participated. Intervention group youth were significantly more likely to ask one or more questions about medications, triggers, and environmental control than usual care youth. Providers were significantly more likely to educate intervention group youth about rescue medications, triggers, and environmental control. Intervention group caregivers were not significantly more likely to ask questions. CONCLUSION: The intervention increased youth question-asking and provider education about medications, triggers, and environmental control. The intervention did not impact caregiver question-asking. PRACTICE IMPLICATIONS: Providers/practices should consider having youth complete question prompt lists and watch the video with their parents before visits to increase youth question-asking during visits.